Vagal influences on respiratory reflexes : interaction of P.S.R. and R.A.R. on the inflation and deflation reflex, their role in linking respiratory cycles : and postvagotomy effect of P.D.G. : a thesis in partial fulfilment of the requirements for the degree of Master of Science, Massey University - Jones, Heather (Massey University, 1985)
There is evidence that changes in one respiratory cycle may influence subsequent cycles by a central mechanism. Thus the influence of P.S.R. and R.A.R. activity from within one respiratory cycle on subsequent cycles, which we have called "memory", needed to be examined in the determination of duration of expiration (tE) and inspiration (tI). this study was designed to investigate the relative roles of P.S.R. and R.A.R. stimulation in expiration influencing tI arnd tE over several subsequent breaths. In particular to investigate their role in linking respiratory cycles. In 14 anaesthetized spontaneously breathing rabbits we studied the response of tI and tE to +ve and -ve pressure pulses of 20KPa applied to the lung at various stages in expiration before and during P.S.R. block with S02. Before P.S.R. block, +ve pressure pulses early in expiration generally shortened tE containing the pulse, applied later +ve pressure pulses lengthened tE. Positive pressure pulses after P.S.R. block, and -ve pressure pulses before and after block always shortened tE. Regardless of sign of pulse tE was shortened in subsequent breaths before and after block. The inspiration after negative pulse application was usually lengthened. After effective block -ve pulses rarely lengthened tl. Large shortening of tE containing the pulse was usually followed bv a shortened tl. Positive pulses did not significantly effect the duration of tl. Regardless of sign of pulse tl was not usually changed but occasional large shortening occured in subsequent breaths before and after P.S.R. block. This indicates that the tE containing the stimulation is governed by a balance between P.S.R. and R.A.R. activity. The tI following t.he stimulus is governed by a balance between memory 11 of P.S.R. and R.A.R. activity. In the breaths following both tE and tI were influenced by memory of R.A.R. activity only. However "memory'' of strong R.A.R. activity is required to affect tI. During this study it was intended to use phenyldiguanide (P.D.G.) to test J receptor patency. Intravenous injections of P.D.G. have been used to provoke respiratory reflexes, these have been considered to be due mainly to stimulation of type J receptors. However although most workers demonstrated that vagotomy abolished or reduced these reflexes, some still had significant response to P.D.G. after vagotomy. A study was conducted to resolve this difference and demonstrate the sites at which P.D.G. acts in rabbits. We measured tE and tI in 10 anaesthetized spontaneously breathing rabbits. 50 g/kg P.D.G. was given intravenously (via a catheter with its tip close to the right atrium) to the intact rabbit; after blocking epicardial receptors; immediately after bilateral cervical vagotomy; 15 minutes after vagotomy; and after the glossopharyngeal nerves were cut near the base of the skull. The respiratory reflex after injection of xylocaine, 15 minutes after vagotomy, and after cutting the glossopharyngeal nerves was as pronounced as in the intact state, and consisted of an increase in frequency almost totally due to a reduction in tE. With injections given up to 3 minutes after bilateral vagotomy the respiratory response was greatly attenuated and variable. We suggest this question of timing may contribute to the differences seen by different groups of workers. It is clear that intravenous injection of P.D.G. is not an adequate test of J receptor presence in the rabbit.
Appendix B - publications can be viewed in the print copy at the libary.
Keywords: Respiration; Regulation; Vagus nerve